Penatalaksanaan Fisioterapi pada Kasus Post Stroke Hemiparese Dextra dengan Modalitas Stimulasi Taktil dan Core Stability di Klinik Ra Hoft - Rahman, Dede; Hadi, Putra; Faridah, Faridah (3031-8572, 2024)
Stroke is a condition where clinical signs develop rapidly in the form of focal and global neurologic deficits, which can be severe and last for 24 hours or more and or can cause death, without any other obvious cause other than vascular. This case study aims to determine the management of tactile stimulation and core stability in reducing sensory disturbances, increasing muscle strength, and increasing functional activity, usually starting exercise for at least a few minutes. The method used is a case study method with one respondent using a sensory measuring instrument with a sensibility test, muscle strength with MMT and ADL with index Katz. after physiotherapy with intervention of tactile stimulation and core stability. During 6 times of therapy, the results were decreased sensory disturbances, increased muscle strength, and increased functional activity. The conclusion of this study is that with the complaints caused by these conditions, the authors chose the intervention of tactile stimulation and Core Stability therapy for 6 therapy times. The results were a decrease in sensory disturbances, an increase in muscle strength, and an increase in functional activity.